Surprising Attraction of Non-Magnetic Materials to Magnets - Vo, Tin Trung; Pollack, Gerald (JOURNAL OF ADVANCES IN PHYSICS, 2018)
We explored the effects of static magnetic fields on materials commonly classified as non-ferromagnetic and non-paramagnetic. By floating pieces of paper, wood, Teflon, and Nafion on different liquids and placing those objects near a neodymium magnet, we found that the objects moved consistently towards the magnet. As the distance between object and magnet diminished, the attraction strengthened. The results imply that objects currently classified as non-magnetic may in fact be at least weakly magnetic.